Upaya Pemanfaatan Limbah Ikan Senangin (Eleutheronema tetradactylum) dalam Pembuatan Stik Sebagai Sumber Pangan Bergizi - wafiqotul isma; Maghfiroh, Khoirin; Pamungkas, Pinctada Putri (Fishery Product Technology Study Program, Yudharta University, Pasuruan, 2024)
In an effort to reduce waste and maximize resources, the use of sengin fish waste is processed into healthy and delicious fish stick products. The aim of making fish sticks is to optimize the use of sukain fish waste which has not been used properly, reduce the environmental impact caused by fishery waste, and provide a nutritious food alternative that is economical and easily accessible to the public. This research method includes 1 sample P0 (control) using 50 grams of fish bones and 3 treatments, namely P1 with the addition of 75 grams of fish bones, P2 with the addition of 100 grams of fish bones and P3 with the addition of 125 grams of fish bones. The effect of adding fish bone meal on organoleptic tests showed that the highest average results were in treatment 1 (P1) (3.63), P2 (3.51) and P3 (3.36). In terms of color, P1 is preferred because it is not too brownish. The higher the addition of fish bones, the more dull brown the color of the stick will be. Of the flavors, P1 liked the most because the spices were more pronounced or balanced and were not disguised by the larger number of fish bones. From the aroma, P2 is more preferred because P2 provides sufficient aroma and is liked by the majority of consumers, while P1 is too low and P3 is too high in aroma intensity. In terms of texture, P1 and P2 are more preferred because there is a good balance so the results are similar and in P3 (125 grams) there is an increase in fish bone flour which can make the layers thicker or different so that they are harder